2017 Ieee Sensors 2017
DOI: 10.1109/icsens.2017.8234202
|View full text |Cite
|
Sign up to set email alerts
|

Floor sensors of animal weight and gait for precision livestock farming

Abstract: Abstract-We report first results on developing smart sensor systems for the automatic and frequent collection of animal weight and gait data, under the hostile conditions of a livestock farm. The novelty in our approach is to sense frequently the animals' floor contact, in suitably chosen locations, under natural and unobtrusive conditions. We demonstrate a pilot low profile rubberized mat sensor heads, delivering a large number of plastic optical fiber transmission measurements taken frequently from individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Vaughan et al [131] developed animal weight and gait sensors on the floor for precision livestock farming. The author suggested that pig farms may use low-cost, lowmaintenance, and low-profile sensor mats to track the pigs' stride and weight.…”
Section: Iot In Agriculturementioning
confidence: 99%
“…Vaughan et al [131] developed animal weight and gait sensors on the floor for precision livestock farming. The author suggested that pig farms may use low-cost, lowmaintenance, and low-profile sensor mats to track the pigs' stride and weight.…”
Section: Iot In Agriculturementioning
confidence: 99%
“…More recent research has investigated smart floors in applications ranging from entertainment [17], to elderly healthcare and monitoring [18], mental health [19], identification and tracking [20], indoor navigation [21], as well as uses as a non-human interface for robots [22] and livestock [23]. Others have looked at the intricacies of human anatomy, and in particular the feet, in regard to human computer interaction [24].…”
Section: Background and Related Workmentioning
confidence: 99%
“…A profitability is a measurement of receipts minus costs and it is depending on the economic efficiency of productivity. Meanwhile, FCR is a ratio of feed intake (feed usage) into live weight and provides a benchmark of management performance (productivity), as well as profitability of each given feed cost [7][8]. Constantly, a productivity improvement will increase profit, through its effect on the way inputs are transformed into outputs and hence, more outputs (revenue) will be produced from the same inputs (same costs).…”
Section: Introductionmentioning
confidence: 99%